Carbon Dioxide and Methane Emissions from Eutrophic, Vegetated Coastal Lagoons Potentially Offset Carbon Accumulation in Eelgrass Sediments - C. Wigand; S. Ayvazian; N. Bartolucci; A. Beardwood; S. Miller; D. Cobb; P. Colarusso; N. Merrill; K. Miller (Estuaries and Coasts, 2026)

Incorporating experiments into management to facilitate rapid learning about climate change adaptation - Christopher P. Nadeau; A. Randall Hughes; Eric G. Schneider; Phil Colarusso; Nicholas A. Fisichelli; Abraham J. Miller-Rushing (Biological Conservation, 2024)

Correction to: Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)

Factors Influencing Carbon Stocks and Accumulation Rates in Eelgrass Meadows Across New England, USA - A. B. Novak; M. C. Pelletier; P. Colarusso; J. Simpson; M. N. Gutierrez; A. Arias-Ortiz; M. Charpentier; P. Masque; P. Vella (Estuaries and Coasts, 2020)
Increasing the protection of coastal vegetated ecosystems has been suggested as one strategy to compensate for increasing carbon dioxide (CO 2 ) in the atmosphere as the capacity of these habitats to sequester and store carbon exceeds that of terrestrial habitats. Seagrasses are a group of foundation species that grow in shallow coastal and estuarine systems and have an exceptional ability to sequester and store large quantities of carbon in biomass and, particularly, in sediments. However, carbon stocks (C org stocks) and carbon accumulation rates (C org accumulation) in seagrass meadows are highly variable both spatially and temporally, making it difficult to extrapolate this strategy to areas where information is lacking. In this study, C org stocks and C org accumulation were determined at 11 eelgrass meadows across New England, representing a range of eutrophication and exposure conditions. In addition, the environmental factors and structural characteristics of meadows related to variation in C org stocks were identified. The objectives were accomplished by assessing stable isotopes of δ 13 C and δ 15 N as well as %C and %N in plant tissues and sediments, measuring grain size and 210 Pb of sediment cores, and through assessing site exposure. Variability in C org stocks in seagrass meadows is well predicted using commonly measured environmental variables such as grain size distribution. This study allows incorporation of data and insights for the northwest Atlantic, where few studies on carbon sequestration by seagrasses have been conducted.

A survey of dioxins (PCDDs and PCDFs) and dioxin-like PCBs in sheep and goat milk from Campania, Italy - M. Esposito; F.P. Serpe; S. Cavallo; R. Pellicanò; P. Gallo; G. Colarusso; R. D’ambrosio; L. Baldi; G. Iovane; L. Serpe (Food Additives & Contaminants Part B-Surveillance, 2010)